A Comparative Profile of Free Radicals, Endogenous Antioxidants, and Cytokines in Mouse Model of Type 1 Diabetes Mellitus - Fikriya Novita Sari; Rizky Senna Samoedra; Setyaki Kevin Pratama; Sri Rahayu; Aris Soewondo; Muhaimin Rifa'i (Universitas Brawijaya, 2023)
Diabetes mellitus is a metabolic disorder characterized by high blood glucose (hyperglycemia). Hyperglycemia will cause the body to undergo physiological changes such as free radical, antioxidant and inflammation alteration. This research aims to compare the profile of free radicals, endogenous antioxidants, and cytokines in mouse models of type 1 diabetes mellitus (T1DM). Mice were separated into two different groups, normal and diabetic mice groups. The normal group was a group of mice that were not induced to have diabetic conditions, while the diabetic mice group was induced to be diabetic using streptozotocin injection. Blood glucose levels were checked every three days for 14 days, while the immune response was evaluated after 14 days using flow cytometry. Data analysis was done using SPSS software with t-test analysis. This research showed that the increasing ROS represented by MDA would trigger inflammation in T1DM represented by the increasing TNF-alpha along with IFN-gamma and reducing anti-inflammatory cytokines represented by IL-10. Interestingly, SOD expression, which is an endogenous antioxidant, is also increased in the diabetic mice group, and we conclude that it is some sort of adaptive response of the diabetic mice group against the increasing ROS.